O encontro com Cristo nas ações litúrgicas: no contexto da modernidade líquida - Neves, Marcos Vieira das (2018)
All current life is an encounter and it happens between two parts, ‘I’ and ‘another’, being this another ‘You’ or one ‘That’. The meeting takes place in a context, that today is the liquid modernity, that radically changed the way to relate. In this sense the encounter with Christ in the liturgical actions transforms the human being and take the have a new life in Him, which, therefore, it also transforms the world. In this sense, the aim of this paper is to lecture on the concepts to the meeting, net modernity and its challenges for the meeting, presence and encounter with Christ in the liturgy and culture of the meeting as a way of overcoming the current world. For it was made a bibliographical research in the works of authors with, Buber, Bauman, Giraudo, Rahner, as well as in magisterium and commentators alike. As a result, has drawn up a vision on the concept of a philosophical and theological point of view, as well as an approach of aspects of liquid modernity and its challenges, in addition to an investigation of the meeting and presence of Christ in its five forms in the liturgy, as exposed by the Sacrosanctum Concilium. It also reached that the meetings in the liturgical actions provoke the 'meeting culture' that overcomes the challenges of the modern liquid world. Thus it is concluded that the change of individual mentality, which is necessarily added with that of other human beings, It is essential to the culture of the meeting and that some steps can be fleshed out to that, such as issue of laypeople christians, the inculturation and young people